Indonesia’s Capital Relocation: A Normative-Juridical Review of Governmental, Criminal Law, and State Stability - Ananda Selly Manila Wati; Setiyawan, Deni (Fakultas Syariah INSURI Ponorogo, 2025)
The relocation of the National Capital has become a strategic issue and a legal urgency in Indonesia due to its impact on governmental stability, legal order, and national security. Emerging issues include the government's authority in determining the location of the National Capital, potential legal conflicts between national and international regulations, and the risk of criminal law violations in land acquisition and project implementation. This study aims to analyze the juridical aspects of the National Capital relocation by integrating perspectives from administrative law, criminal law, and the stability of the Unitary State of the Republic of Indonesia (NKRI). The research employs a normative-juridical method with legislative, case study, and conceptual approaches. The results indicate that the relocation of the National Capital must consider legality based on Law Number 3 of 2022 concerning the National Capital, principles of good governance, and the prevention of criminal acts related to land acquisition and development. The integration of administrative and criminal law is crucial for maintaining political, social, and economic stability. In conclusion, the relocation of the National Capital is legally valid if carried out with strict adherence to legal compliance, transparent oversight, and effective mechanisms for mitigating criminal risk, thereby supporting the sustainable stability of the Republic of Indonesia.